2019
DOI: 10.3892/etm.2019.7559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of etanercept, a tumor necrosis factor receptor fusion protein, on primary cell cultures prepared from intact human intervertebral disc tissue

Abstract: The aim of the present study was to investigate the effects of etanercept (ETA), a tumor necrosis factor (TNF) inhibitor, on human cell cultures prepared from intact intervertebral disc tissue. ETA is used as a treatment for cases of rheumatoid arthritis, psoriatic arthritis, axial spondyloarthritis and ankylosing spondylitis accompanied by moderate or severe joint pain. ETA was applied to primary cell cultures [annulus fibrosus and nucleus pulposus (NP) from intact intervertebral disc tissue]. Cell cultures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…A clinical study showed that single intradiscal administration of 10 mg Etanercept on patients with LBP could alleviate pain levels for 8 weeks after follow-up (Sainoh et al, 2016). Furthermore, Caliskan and coworkers investigated the effect of Etanercept on primary cell cultures (first-passage cultures of NP and AF cells) from intact human IVD tissue at doses of 0.1, 0.25, 0.5, 1, and 2 mg/mL (Caliskan et al, 2019). The Etanercept doses of >0.5 mg/mL were found to have cytotoxic effects.…”
Section: Anti-inflammatory Therapy Via Etanercept or Tofacitinibmentioning
confidence: 99%
“…A clinical study showed that single intradiscal administration of 10 mg Etanercept on patients with LBP could alleviate pain levels for 8 weeks after follow-up (Sainoh et al, 2016). Furthermore, Caliskan and coworkers investigated the effect of Etanercept on primary cell cultures (first-passage cultures of NP and AF cells) from intact human IVD tissue at doses of 0.1, 0.25, 0.5, 1, and 2 mg/mL (Caliskan et al, 2019). The Etanercept doses of >0.5 mg/mL were found to have cytotoxic effects.…”
Section: Anti-inflammatory Therapy Via Etanercept or Tofacitinibmentioning
confidence: 99%
“…CHAD proteins bind to integrins, cell surface proteoglycans, and COL2A1; they play a role in regulating chondrocyte signaling and cartilage homeostasis. COL2A1 is an important cartilage-specific matrix protein, and the existence of COL2A1 in normal cartilage is a marker for anabolism [15, 16]. COL2A1 gene expression is regulated by transcription or growth factors, and an increased expression of this gene leads to the induction of ECM production [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…COL2A1 is an important cartilage-specific matrix protein, and the existence of COL2A1 in normal cartilage is a marker for anabolism [15, 16]. COL2A1 gene expression is regulated by transcription or growth factors, and an increased expression of this gene leads to the induction of ECM production [15, 16]. HIF1 is a transcription factor that regulates the transcription of a wide range of genes involved in cell survival [9, 12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations